Laser additive manufacturing method of 316L + xCu functional gradient composite material
By depositing gradient layers with different pure copper powder contents layer by layer on the 316L stainless steel substrate, the problem of insufficient heat dissipation and corrosion resistance of 316L stainless steel materials is solved, high bonding strength and excellent thermal conductivity are achieved, and the application range of materials is expanded.
Patent Information
- Application Number
- CN202411270114.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-11
- Publication Date
- 2024-12-27
AI Technical Summary
A single 316L stainless steel material cannot meet the growing heat dissipation needs, and service life is affected due to intergranular corrosion, and the mismatch between Cu and 316L thermal conductivity and laser absorption leads to a reduced interface bonding intensity.
Laser additive manufacturing method using 316L+xCu functional gradient composite material, by aerosolized 316L powder and pure copper powder are arranged into multiple gradient composite materials in different proportions, and deposited layer by layer on the 316L stainless steel substrate, using laser The additive manufacturing equipment performs scanning and melting deposition under an inert gas environment to form a gradient layer with different pure copper powder contents, improves the temperature gradient and cooling rate, and reduces thermal stress.
The 316L+xCu functional gradient composite material has been achieved with good thermal conductivity and corrosion resistance. The adjacent gradient layer has high bond strength, which broadens the application field of materials and improves the freedom of mechanical properties and component design through in-situ heat treatment.
Smart Images

Figure CN119187593A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of laser additive manufacturing of gradient materials, and in particular to a laser additive manufacturing method of a 316L+xCu functional gradient composite material. Background Art
[0002] 316L stainless steel is widely used in the industrial field due to its excellent mechanical properties. However, a single 316L stainless steel material can no longer meet the growing demand for heat dissipation, and the service life of the stainless steel is also affected by intergranular corrosion. Cu has low strength and hardness, but has excellent thermal conductivity. The two materials can work synergistically to give full play to their respective advantages, optimize the microstructure, and improve thermal conductivity and corrosion resistance. However, the mismatch in thermal conductivity and laser absorptivity between the two will lead to a decrease in the interface bonding strength of the direct connection. Summary of the invention
[0003] The main purpose of the present invention is to propose a laser additive manufacturing method for 316L+xCu functional gradient composite materials to solve the above technical problems.
[0004] To achieve the above object, the present invention proposes a laser additive manufacturing method for a 316L+xCu functionally gradient composite material, comprising the following steps:
[0005] Step S1, atomizing 316L powder and pure copper powder are configured into four gradient composite materials, namely, a first gradient composite material, a second gradient composite material, a third gradient composite material and a fourth gradient composite material in different proportions, wherein the content of pure copper powder in the four gradient materials increases in sequence, and the content of pure copper powder in the first gradient composite material is 0, and the content of pure copper powder in the fourth gradient composite material is less than 10wt%;
[0006] Step S2, pre-treating the 316L stainless steel substrate;
[0007] Step S3: Using laser additive manufacturing equipment, the first gradient composite material, the second gradient composite material, the third gradient composite material and the fourth gradient composite material are deposited layer by layer on the 316L stainless steel substrate in sequence according to preset process parameters to obtain a 316L+xCu functional gradient composite material.
[0008] Furthermore, the content of pure copper powder in the second gradient composite material is 3wt%, the content of pure copper powder in the third gradient composite material is 5wt%, and the content of pure copper powder in the fourth gradient composite material is 8wt%.
[0009] Furthermore, the step S1 specifically includes:
[0010] Step S11, drying the atomized 316L powder and the pure copper powder;
[0011] Step S12: mechanically mixing the dried atomized 316L powder and the pure copper powder in different proportions in sequence to obtain the first gradient composite material, the second gradient composite material, the third gradient composite material and the fourth gradient composite material.
[0012] Furthermore, the step S2 specifically includes:
[0013] The surface of the 316L stainless steel substrate was polished using silicon carbide sandpaper.
[0014] Furthermore, the laser additive manufacturing equipment includes a fiber laser, a powder feeder and a protective gas tank, the wavelength of the fiber laser is 1064nm, and the protective gas tank stores an inert gas.
[0015] Furthermore, the step S3 specifically includes:
[0016] Step S31, according to the preset process parameters, under the inert gas output by the protective gas tank, using the fiber laser to scan, melt and deposit the first gradient composite material output by the powder feeder on the 316L stainless steel substrate to obtain a first gradient layer;
[0017] Step S32, according to the preset process parameters, under the inert gas output by the protective gas tank, using the fiber laser to scan, melt and deposit the second gradient composite material output by the powder feeder on the first gradient layer to obtain a second gradient layer;
[0018] Step S33, according to the preset process parameters, under the inert gas output by the protective gas tank, using the fiber laser to scan, melt and deposit the third gradient composite material output by the powder feeder on the second gradient layer to obtain a third gradient layer;
[0019] Step S34, according to the preset process parameters, under the inert gas output by the protective gas tank, use the fiber laser to scan, melt and deposit the fourth gradient composite material output by the powder feeder on the third gradient layer to obtain a fourth gradient layer.
[0020] Furthermore, the height of the first gradient layer, the height of the second gradient layer, the height of the third gradient layer and the height of the fourth gradient layer are 2.5 mm respectively.
[0021] Furthermore, the preset process parameters in step S3 are specifically as follows: the laser power of the fiber laser is 500 W, the laser scanning speed is 600 mm / min, the laser scanning spacing is 0.8 mm, the powder feeding rate of the powder feeder is 14.12 g / min, and the gas delivery volume of the protective gas tank is 15 L / min.
[0022] Furthermore, after step S3, the following steps are further included:
[0023] Step S4, analyzing and measuring the 316L+xCu functional gradient composite material.
[0024] Furthermore, the step S4 specifically includes:
[0025] Step S41, performing electric spark wire cutting on the 316L+xCu functional gradient composite material to obtain two test samples, and grinding and polishing the two test samples;
[0026] Step S42, observing the microstructure of one of the two test samples using a scanning electron microscope;
[0027] Step S43, using an electrochemical three-electrode measurement system to perform a potentiodynamic polarization curve test and an AC impedance spectrum measurement on the other of the two test samples and the comparison sample, wherein the comparison sample is a 316L material obtained by scanning melting deposition of aerosolized 316L powder according to the preset process parameters.
[0028] In the technical solution of the present invention, the 316L+xCu functional gradient composite material is prepared by laser additive manufacturing equipment, and the atomized 316L powder and pure copper powder are configured in different proportions to obtain a first gradient composite material, a second gradient composite material, a third gradient composite material and a fourth gradient composite material, which are deposited layer by layer on the 316L stainless steel substrate in sequence according to preset process parameters; in this way, the temperature gradient and the cooling rate can be improved by the gradient distribution with different pure copper powder contents, and the thermal stress can be reduced layer by layer, so that the 316L+xCu functional gradient composite material presents a gradually transitional microstructure along the deposition direction, and the bonding strength between two adjacent gradient layers is high, and it has good thermal conductivity and corrosion resistance, which broadens the application field of 316L and Cu; at the same time, it is prepared by laser additive manufacturing technology, which is simple to operate, has a short production cycle, is easy to realize customized performance materials and accurately control the supply ratio of different materials, improves the degree of freedom of component design, and the in-situ heat treatment effect produced is crucial to preventing defect formation, microstructural characteristics and mechanical properties of the produced components. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying creative work.
[0030] Figure 1 A flow chart of the laser additive manufacturing method of the 316L+xCu functionally gradient composite material provided by the present invention;
[0031] Figure 2 for Figure 1 Flow chart of step S1 in FIG.
[0032] Figure 3 for Figure 1 Flow chart of step S3;
[0033] Figure 4 for Figure 1 Flow chart of step S4;
[0034] Figure 5 Schematic diagram of preparing 316L+xCu functionally graded composites for laser additive manufacturing equipment;
[0035] Figure 6 Scanning electron microscope (SEM) images of four gradient layers in a 316L+xCu functionally gradient composite material prepared by a laser additive manufacturing method for a 316L+xCu functionally gradient composite material provided by the present invention;
[0036] Figure 7 for Figure 6 Scanning electron microscope (SEM) image of the junction of four gradient layers in the 316L+xCu functional gradient composite material prepared in ;
[0037] Figure 8 for Figure 6 Potentiodynamic polarization curves of the 316L+xCu functional gradient composite material and the comparative sample prepared in 0.5 mol / L dilute sulfuric acid solution;
[0038] Fig. 9 for Figure 6 Nyquist plots of electrochemical impedance spectroscopy of the 316L+xCu functionally gradient composite material prepared in 0.5 mol / L dilute sulfuric acid solution and the comparative sample;
[0039] Fig.10 for Figure 6Bode plots of electrochemical impedance spectroscopy of the 316L+xCu functionally gradient composite material prepared and the comparison sample in 0.5 mol / L dilute sulfuric acid solution.
[0040] Description of Figure Numbers:
[0041]
[0042] The realization of the purpose, functional features and advantages of the present invention will be further explained in conjunction with embodiments and with reference to the accompanying drawings. DETAILED DESCRIPTION
[0043] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0044] It should be noted that if the embodiments of the present invention involve directional indications (such as up, down, left, right, front, back, etc.), the directional indications are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as shown in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.
[0045] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of technical features indicated. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In addition, the meaning of "and / or" appearing in the full text includes three parallel schemes. Taking "A and / or B" as an example, it includes scheme A, or scheme B, or a scheme that satisfies both A and B. In addition, the technical solutions between the various embodiments can be combined with each other, but it must be based on the ability of ordinary technicians in the field to implement. When the combination of technical solutions is contradictory or cannot be implemented, it should be deemed that such a combination of technical solutions does not exist and is not within the scope of protection required by the present invention.
[0046] 316L stainless steel is widely used in the industrial field due to its excellent mechanical properties. However, a single 316L stainless steel material can no longer meet the growing demand for heat dissipation, and the service life of the stainless steel is also affected by intergranular corrosion. Cu has low strength and hardness, but has excellent thermal conductivity. The two materials can work synergistically to give full play to their respective advantages, optimize the microstructure, and improve thermal conductivity and corrosion resistance. However, the mismatch in thermal conductivity and laser absorptivity between the two will lead to a decrease in the interface bonding strength of the direct connection.
[0047] In view of this, the present invention provides a laser additive manufacturing method for a 316L+xCu functionally gradient composite material. Figures 1 to 4 A flow chart provided for the present invention.
[0048] See also Figure 1 The laser additive manufacturing method of the 316L+xCu functional gradient composite material comprises the following steps:
[0049] Step S1, atomized 316L powder and pure copper powder are configured into four gradient composite materials, namely, a first gradient composite material, a second gradient composite material, a third gradient composite material and a fourth gradient composite material in different proportions, wherein the content of pure copper powder in the four gradient materials increases successively, and the content of pure copper powder in the first gradient composite material is 0, and the content of pure copper powder in the fourth gradient composite material is less than 10wt%.
[0050] For further information, see Figure 2 , the step S1 specifically comprises:
[0051] Step S11, drying the atomized 316L powder and the pure copper powder.
[0052] In this step, the atomized 316L powder and the pure copper powder were dried at 120° C. for 2 h using a vacuum dryer.
[0053] Step S12: mechanically mixing the dried atomized 316L powder and the pure copper powder in different proportions in sequence to obtain the first gradient composite material, the second gradient composite material, the third gradient composite material and the fourth gradient composite material.
[0054] In this step, a planetary ball mill is used to operate at a speed of 150 r / min for 2 hours to mix the aerosolized 316L powder and the pure copper powder without balls, so that the spherical morphology of the aerosolized 316L powder is maintained, thereby ensuring that the powder has good fluidity.
[0055] Step S2: pre-treating the 316L stainless steel substrate 300.
[0056] Furthermore, the step S2 specifically includes:
[0057] The surface of the 316L stainless steel substrate 300 is polished with silicon carbide sandpaper.
[0058] More specifically, the use of 280# silicon carbide sandpaper for grinding is conducive to forming a strong interface and adhesion between the surface of the 316L stainless steel substrate 300 and the molten gradient composite material.
[0059] Furthermore, after polishing, the surface of the 316L stainless steel substrate 300 is wiped clean with alcohol and dried.
[0060] It should be noted that, in the present invention, the order of step S1 and step S2 is not critical.
[0061] Step S3, using a laser additive manufacturing device 100, depositing the first gradient composite material, the second gradient composite material, the third gradient composite material and the fourth gradient composite material layer by layer on the 316L stainless steel substrate 300 in sequence according to preset process parameters to obtain a 316L+xCu functional gradient composite material 200.
[0062] For details, please refer to Figure 5 The laser additive manufacturing device 100 includes a fiber laser 110, a powder feeder 120 and a protective gas tank 130. The wavelength of the fiber laser 110 is 1064 nm, and the protective gas tank 130 stores an inert gas. More specifically, the powder feeder 120 and the protective gas tank 130 are connected to the fiber laser 110, respectively.
[0063] The working principle of the laser additive manufacturing device 100 is as follows: driven by the inert gas in the protective gas tank 130, the powder in the gradient composite material converges to a point on the deposition surface through three different paths. Under the irradiation of the laser emitted by the laser head of the fiber laser 110, the powder melts and forms a small molten pool; when the laser head moves in a directional manner, the molten pool solidifies rapidly, and under the protection of the inert gas, the molten pool is not oxidized during the solidification process.
[0064] For further information, see Figure 3 , the step S3 specifically includes:
[0065] Step S31, according to the preset process parameters, under the inert gas output by the protective gas tank 130, the first gradient composite material output by the powder feeder 120 is scanned, melted and deposited on the 316L stainless steel substrate 300 by the fiber laser 110 to obtain a first gradient layer 210.
[0066] In this step, the first gradient composite material is first loaded into the powder feeder 120, and then after being scanned, melted and deposited on the 316L stainless steel substrate 300 by the fiber laser 110, the powder on the barrel wall of the powder barrel of the powder feeder 120 and the powder on the powder feeding tube are cleaned by inert gas.
[0067] Step S32 , according to the preset process parameters, under the protective gas output by the protective gas tank 130 , use the fiber laser 110 to scan, melt and deposit the second gradient composite material output by the powder feeder 120 on the first gradient layer 210 to obtain a second gradient layer 220 .
[0068] In this step, before laser scanning melting deposition is performed, the second gradient composite material is first loaded into the cleaned powder feeder 120, and after the deposition of the second gradient layer 220 is completed, the powder feeder 120 is cleaned by an inert gas.
[0069] Step S33 , according to the preset process parameters, under the protective gas output by the protective gas tank 130 , use the fiber laser 110 to scan, melt and deposit the third gradient composite material output by the powder feeder 120 on the second gradient layer 220 to obtain a third gradient layer 230 .
[0070] In this step, before laser scanning melting deposition is performed, the third gradient composite material is first loaded into the cleaned powder feeder 120, and after the deposition of the third gradient layer 230 is completed, the powder feeder 120 is cleaned by an inert gas.
[0071] Step S34 , according to the preset process parameters, under the protective gas output by the protective gas tank 130 , use the fiber laser 110 to scan, melt and deposit the fourth gradient composite material output by the powder feeder 120 on the third gradient layer 230 to obtain a fourth gradient layer 240 .
[0072] In this step, before laser scanning melting deposition is performed, the fourth gradient composite material is first loaded into the cleaned powder feeder 120 .
[0073] For details, please refer to Figure 1 , after step S3, the step further includes:
[0074] Step S4, analyzing and measuring the 316L+xCu functional gradient composite material 200.
[0075] In this step, the bonding strength between the gradient layers in the prepared 316L+xCu functional gradient composite material 200 and the corrosion resistance of the 316L+xCu functional gradient composite material 200 are determined by analytical measurement.
[0076] For further information, see Figure 4 , the step S4 specifically includes:
[0077] Step S41, performing electric spark wire cutting on the 316L+xCu functional gradient composite material 200 to obtain two test samples, and then grinding and polishing the two test samples.
[0078] In this step, the test sample is ground and polished using a metallographic sample preparation method.
[0079] Step S42, observing the microstructure of one of the two test samples using a scanning electron microscope;
[0080] Step S43, using an electrochemical three-electrode measurement system to perform a potentiodynamic polarization curve test and an AC impedance spectrum measurement on the other of the two test samples and the comparison sample, wherein the comparison sample is a 316L material obtained by scanning melting deposition of aerosolized 316L powder according to the preset process parameters.
[0081] In this step, the comparative sample is obtained by scanning, melting and depositing the atomized 316L powder on another 316L stainless steel substrate using the fiber laser according to the preset process parameters.
[0082] It should be noted that, in the present invention, the order of step S42 and step S43 is not critical.
[0083] Furthermore, the step S42 specifically includes:
[0084] Step S421: corrode one of the two test samples using aqua regia.
[0085] Step S422: using the scanning electron microscope to observe the microstructures of the first gradient layer 210, the second gradient layer 220, the third gradient layer 230 and the fourth gradient layer 240 in the test sample.
[0086] In this step, the evolution of the microscopic components of the 316L+xCu functionally gradient composite material 200 along with the distribution of the four gradient layers is obtained by observation.
[0087] Step S423: Use the scanning electron microscope to observe the microstructure of the junction of the first gradient layer 210 and the second gradient layer 220, the microstructure of the junction of the second gradient layer 220 and the third gradient layer 230, and the microstructure of the junction of the third gradient layer 230 and the fourth gradient layer 240 in the test sample.
[0088] In this step, by observing the microstructure of the junction of two adjacent gradient layers, it is confirmed whether the two adjacent gradient layers are well bonded and whether obvious pores are generated.
[0089] Specifically, the step S43 specifically includes:
[0090] Step S431, grinding and polishing the other one of the two test samples to have a mirror effect.
[0091] Step S432, selecting a dilute sulfuric acid solution as the electrolyte, determining that the open circuit potential is stable, and using the electrochemical three-electrode measurement system to apply a sinusoidal AC signal at a preset frequency to perform an electrochemical impedance spectroscopy test on the test sample and the comparison sample.
[0092] Step S433: using the electrochemical three-electrode measurement system to perform a potentiodynamic polarization curve test on the test sample and the comparison sample at a certain scanning speed.
[0093] In the technical solution of the present invention, the 316L+xCu functional gradient composite material 200 is prepared by laser additive manufacturing equipment 100, and the first gradient composite material, the second gradient composite material, the third gradient composite material and the fourth gradient composite material are obtained by configuring the atomized 316L powder and the pure copper powder in different proportions, and depositing them layer by layer on the 316L stainless steel substrate 300 in sequence according to preset process parameters; in this way, the temperature gradient and the cooling rate are improved by the gradient distribution with different pure copper powder contents, and the thermal stress is reduced layer by layer. The 316L+xCu functional gradient composite material 200 presents a gradually transitional microstructure along the deposition direction, and the bonding strength between two adjacent gradient layers is high, and it has good thermal conductivity and corrosion resistance, which broadens the application field of 316L and Cu; at the same time, it is prepared by laser additive manufacturing technology, which is simple to operate, has a short production cycle, is easy to realize customized performance materials and accurately control the supply ratio of different materials, improves the degree of freedom of component design, and the in-situ heat treatment effect produced is crucial to preventing defect formation, microstructural characteristics and mechanical properties of the produced components.
[0094] In order to deepen the understanding of the present invention, the present invention will be further described in detail below with reference to the embodiments.
[0095] Embodiment 1:
[0096] The laser additive manufacturing method of the 316L+xCu functionally gradient composite material comprises the following steps:
[0097] Step S1. First, use a vacuum dryer to dry the atomized 316L powder and the pure copper powder at 120°C for 2 hours, and then use a planetary ball mill to run the dried atomized 316L powder and the pure copper powder in different proportions for mechanical mixing at a speed of 150r / min for 2 hours to obtain a uniformly mixed powder, namely the first gradient composite material, the second gradient composite material, the third gradient composite material and the fourth gradient composite material, wherein the content of pure copper powder in the four gradient materials is set to: the content of pure copper powder in the first gradient composite material is 0, the content of pure copper powder in the second gradient composite material is 2wt%, the content of pure copper powder in the third gradient composite material is 4wt%, and the content of pure copper powder in the fourth gradient composite material is 6wt%.
[0098] Step S2: polishing the surface of the 316L stainless steel substrate 300 with 280# silicon carbide sandpaper.
[0099] Step S3, using a laser additive manufacturing device 100, depositing the first gradient composite material, the second gradient composite material, the third gradient composite material and the fourth gradient composite material layer by layer on the 316L stainless steel substrate 300 in sequence according to preset process parameters to obtain a 316L+xCu functional gradient composite material 200.
[0100] Specifically, first, the first gradient composite material is loaded into the powder feeder 120, and according to the preset process parameters, the laser power of the fiber laser 110 is set to 500 W, the laser scanning speed is set to 600 mm / min, the laser scanning interval is set to 0.8 mm, the powder feeding rate of the powder feeder 120 is set to 14.12 g / min, and the gas feeding amount of the protective gas tank 130 is set to 15 L / min. Under the inert gas output by the protective gas tank 130, the first gradient composite material output by the powder feeder 120 is used by the fiber laser 110 in the 3 Scanning melting deposition is performed on a 16L stainless steel substrate 300 to obtain a first gradient layer 210 with a height of 2.5 mm, and the first gradient layer 210 is cooled for 5 minutes to prevent cracks caused by excessive thermal stress; the powder on the barrel wall of the powder barrel of the powder feeder 120 and the powder on the powder feeding tube are cleaned by inert gas, and the second gradient composite material is loaded into the cleaned powder feeder 120. According to the same preset process parameters, under the protective gas output by the protective gas tank 130, the second gradient composite material output by the powder feeder 120 is formed on the first gradient layer 210 by using the optical fiber laser 110. Scanning melting deposition is performed on the second gradient layer 220 to obtain a second gradient layer 220 with a height of 2.5 mm, and the layer is cooled for 5 minutes; then, the powder feeder 120 is cleaned by an inert gas, and the third gradient composite material is loaded into the cleaned powder feeder 120, and according to the same preset process parameters, under the protective gas output by the protective gas tank 130, the fiber laser 110 is used to scan and melt deposit the third gradient composite material output by the powder feeder 120 on the second gradient layer 220 to obtain a third gradient layer 230 with a height of 2.5 mm, and the layer is cooled for 5 minutes; finally Afterwards, the powder on the barrel wall of the powder barrel of the powder feeder 120 and the powder on the powder feeding tube are cleaned by inert gas, and the fourth gradient composite material is loaded into the cleaned powder feeder 120. According to the same preset process parameters, under the protective gas output by the protective gas tank 130, the fiber laser 110 is used to scan, melt and deposit the fourth gradient composite material output by the powder feeder 120 on the third gradient layer 230 to obtain a fourth gradient layer 240 with a height of 2.5 mm, and then cooled for 5 minutes to obtain a 316L+xCu functional gradient composite material 200.
[0101] It should be noted that after each gradient layer is scanned and printed, it is cooled in a closed environment.
[0102] Step S4, performing electric spark wire cutting on the 316L+xCu functional gradient composite material 200 to obtain two test samples, and grinding and polishing the two test samples using a metallographic sample preparation method; then corroding one of the two test samples with aqua regia for 10 seconds, and using the scanning electron microscope to observe the microstructure of the first gradient layer 210, the second gradient layer 220, the third gradient layer 230 and the fourth gradient layer 240 in the test sample, as well as observing the microstructure of the junction of the first gradient layer 210 and the second gradient layer 220 in the test sample, the second gradient layer 230 and the fourth gradient layer 240. The microstructure of the junction of the gradient layer 220 and the third gradient layer 230, and the microstructure of the junction of the third gradient layer 230 and the fourth gradient layer 240 are obtained. In this way, the evolution of the microscopic components of the 316L+xCu functional gradient composite material 200 with the distribution of the four gradient layers is obtained, and it is confirmed whether the two adjacent gradient layers are well combined and whether there are obvious pores. In addition, the other of the two test samples is polished to a mirror effect, and a 0.5 mol / L dilute sulfuric acid solution is selected as the electrolyte to determine that the open circuit potential is stable. The electrochemical three-electrode measurement system is used at a preset frequency of 10 5 Hz~10 -2 At Hz, a sinusoidal AC signal with an amplitude of 10 mV was applied to the test sample and the comparison sample to perform an electrochemical impedance spectroscopy test to determine the corrosion resistance of the 316L+xCu functional gradient composite material 200.
[0103] The analysis and measurement results of the 316L+xCu functional gradient composite material 200 are as follows: from the first gradient layer 210 to the fourth gradient layer 240, the microstructure of the test sample, i.e., the 316L+xCu functional gradient composite material 200, evolves with the gradient distribution, presenting a gradually transitional microstructure, the grains gradually decrease, the two adjacent gradient layers are well bonded, and no obvious pores are generated. As the concentration of pure copper powder increases, the density of the passivation film is effectively improved, and a more stable passivation film is formed compared to the comparison sample, which inhibits the dissolution of the surface of the 316L+xCu functional gradient composite material 200 and has good thermal conductivity and corrosion resistance.
[0104] Embodiment 2:
[0105] The laser additive manufacturing method of the 316L+xCu functionally gradient composite material comprises the following steps:
[0106] Step S1. First, use a vacuum dryer to dry the atomized 316L powder and the pure copper powder at 120°C for 2 hours, and then use a planetary ball mill to run the dried atomized 316L powder and the pure copper powder in different proportions for 2 hours to mechanically mix them, so as to obtain a uniformly mixed powder, namely the first gradient composite material, the second gradient composite material, the third gradient composite material and the fourth gradient composite material, wherein the content of pure copper powder in the four gradient materials is set as follows: the content of pure copper powder in the first gradient composite material is 0, the content of pure copper powder in the second gradient composite material is 3wt%, the content of pure copper powder in the third gradient composite material is 5wt%, and the content of pure copper powder in the fourth gradient composite material is 8wt%.
[0107] Step S2: polishing the surface of the 316L stainless steel substrate 300 with 280# silicon carbide sandpaper.
[0108] Step S3, using a laser additive manufacturing device 100, depositing the first gradient composite material, the second gradient composite material, the third gradient composite material and the fourth gradient composite material layer by layer on the 316L stainless steel substrate 300 in sequence according to preset process parameters to obtain a 316L+xCu functional gradient composite material 200.
[0109] Specifically, first, the first gradient composite material is loaded into the powder feeder 120, and according to the preset process parameters, the laser power of the fiber laser 110 is set to 500 W, the laser scanning speed is set to 600 mm / min, the laser scanning interval is set to 0.8 mm, the powder feeding rate of the powder feeder 120 is set to 14.12 g / min, and the gas feeding amount of the protective gas tank 130 is set to 15 L / min. Under the inert gas output by the protective gas tank 130, the first gradient composite material output by the powder feeder 120 is used by the fiber laser 110 in the 3 Scanning melting deposition is performed on a 16L stainless steel substrate 300 to obtain a first gradient layer 210 with a height of 2.5 mm, and the first gradient layer 210 is cooled for 5 minutes to prevent cracks caused by excessive thermal stress; the powder on the barrel wall of the powder barrel of the powder feeder 120 and the powder on the powder feeding tube are cleaned by inert gas, and the second gradient composite material is loaded into the cleaned powder feeder 120. According to the same preset process parameters, under the protective gas output by the protective gas tank 130, the second gradient composite material output by the powder feeder 120 is formed on the first gradient layer 210 by using the optical fiber laser 110. Scanning melting deposition is performed on the second gradient layer 220 to obtain a second gradient layer 220 with a height of 2.5 mm, and the layer is cooled for 5 minutes; then, the powder feeder 120 is cleaned by an inert gas, and the third gradient composite material is loaded into the cleaned powder feeder 120, and according to the same preset process parameters, under the protective gas output by the protective gas tank 130, the fiber laser 110 is used to scan and melt deposit the third gradient composite material output by the powder feeder 120 on the second gradient layer 220 to obtain a third gradient layer 230 with a height of 2.5 mm, and the layer is cooled for 5 minutes; finally Afterwards, the powder on the barrel wall of the powder barrel of the powder feeder 120 and the powder on the powder feeding tube are cleaned by inert gas, and the fourth gradient composite material is loaded into the cleaned powder feeder 120. According to the same preset process parameters, under the protective gas output by the protective gas tank 130, the fiber laser 110 is used to scan, melt and deposit the fourth gradient composite material output by the powder feeder 120 on the third gradient layer 230 to obtain a fourth gradient layer 240 with a height of 2.5 mm, and then cooled for 5 minutes to obtain a 316L+xCu functional gradient composite material 200.
[0110] It should be noted that after each gradient layer is scanned and printed, it is cooled in a closed environment.
[0111] Step S4, performing electric spark wire cutting on the 316L+xCu functional gradient composite material 200 to obtain two test samples, and grinding and polishing the two test samples using a metallographic sample preparation method; then corroding one of the two test samples with aqua regia for 10 seconds, and using the scanning electron microscope to observe the microstructure of the first gradient layer 210, the second gradient layer 220, the third gradient layer 230 and the fourth gradient layer 240 in the test sample, as well as observing the microstructure of the junction of the first gradient layer 210 and the second gradient layer 220 in the test sample, the second gradient layer 230 and the fourth gradient layer 240. The microstructure of the junction of the gradient layer 220 and the third gradient layer 230, and the microstructure of the junction of the third gradient layer 230 and the fourth gradient layer 240 are obtained. In this way, the evolution of the microscopic components of the 316L+xCu functional gradient composite material 200 with the distribution of the four gradient layers is obtained, and it is confirmed whether the two adjacent gradient layers are well combined and whether there are obvious pores. In addition, the other of the two test samples is polished to a mirror effect, and a 0.5 mol / L dilute sulfuric acid solution is selected as the electrolyte to determine that the open circuit potential is stable. The electrochemical three-electrode measurement system is used at a preset frequency of 10 5 Hz~10 -2 At Hz, a sinusoidal AC signal with an amplitude of 10 mV was applied to the test sample and the comparison sample to perform an electrochemical impedance spectroscopy test to determine the corrosion resistance of the 316L+xCu functional gradient composite material 200.
[0112] For more details, see Figure 6 According to the optical microscope image obtained by the scanning electron microscope, it can be observed that: from the first gradient layer 210 to the fourth gradient layer 240, the microstructure of the 316L+xCu functional gradient composite material 200 evolves with the gradient distribution, presenting a gradually transitional microstructure, specifically: the first gradient layer 210 is a mixture of coarse columnar crystals and honeycomb crystals, the second gradient layer 220 dendrites are refined, and secondary dendrite arms appear. With the increase of the concentration of pure copper powder, the distance between the primary and secondary dendrite arms in the third gradient layer 230 is significantly reduced, and a small amount of equiaxed crystals appear. With the increase of the cladding height, the in-situ heat treatment (IHT) effect is more obvious, and a large number of equiaxed grains are produced in the fourth gradient layer 240. Please refer to Figure 7 According to the optical microscope image obtained by the scanning electron microscope, it can be observed that the two adjacent gradient layers in the 316L+xCu functional gradient composite material 200 are well combined and no obvious pores are generated.
[0113] For further information, see Figure 8According to the potentiodynamic polarization curve, it can be obtained that: compared with the comparative sample, although the 316L+xCu functional gradient composite material 200 has a heterogeneous microstructure, its corrosion resistance is significantly improved, the corrosion potential is -0.022 Vvs.SCE, which is 0.281 Vvs.SCE higher than that of the comparative sample, and the passive current density is 1.88×10 -5 Acm -2 , which is 36% lower than that of the 316L stainless steel substrate 300. It can be inferred that the increase in the concentration of pure copper powder effectively increases the density of the passivation film, thereby inhibiting the dissolution of the surface of the 316L+xCu functional gradient composite material 200.
[0114] Please see again Fig. 9 and Fig.10 According to the AC impedance spectrum, it can be obtained that the capacitance arc radius of the 316L+xCu functional gradient composite material 200 is significantly larger than that of the comparative sample, which indicates that the 316L+xCu functional gradient composite material 200 with a gradient microstructure has excellent corrosion resistance; in addition, the phase angle values of the 316L+xCu functional gradient composite material 200 and the comparative sample are -71° and -63°, respectively, and the passivation film of the 316L+xCu functional gradient composite material 200 with a phase angle closer to -90° has good capacitance characteristics. Further, it can be observed that the 316L+xCu functional gradient composite material 200 has a good capacitance characteristic in the low frequency region (|Z| 0.01Hz ) has an impedance modulus of 6.66×10 4 Ω·cm 2 , which is twice the value of the comparative sample, which reflects that the 316L+xCu functional gradient composite material 200 forms a more stable passivation film than the comparative sample. Combined with the effect of Cu on the microstructure of 316L stainless steel, it can be explained that the high-density grain boundary provides more nucleation sites for the passivation film, and the dense and stable passivation film delays the corrosion of the sample, so that the 316L+xCu functional gradient composite material 200 has excellent corrosion resistance.
[0115] The above description is only a preferred embodiment of the present invention, and does not limit the patent scope of the present invention. All equivalent structural changes made by using the contents of the present invention specification and drawings under the inventive concept of the present invention, or directly / indirectly applied in other related technical fields are included in the patent protection scope of the present invention.
Claims
1. A laser additive manufacturing method for 316L+xCu functionally gradient composite material, characterized in that: The following steps are involved: Step S1, atomizing 316L powder and pure copper powder are configured into four gradient composite materials, namely, a first gradient composite material, a second gradient composite material, a third gradient composite material and a fourth gradient composite material in different proportions, wherein the content of pure copper powder in the four gradient materials increases in sequence, and the content of pure copper powder in the first gradient composite material is 0, and the content of pure copper powder in the fourth gradient composite material is less than 10wt%; Step S2, pre-treating the 316L stainless steel substrate; Step S3: Using laser additive manufacturing equipment, the first gradient composite material, the second gradient composite material, the third gradient composite material and the fourth gradient composite material are deposited layer by layer on the 316L stainless steel substrate in sequence according to preset process parameters to obtain a 316L+xCu functional gradient composite material.
2. The laser additive manufacturing method of the 316L+xCu functionally gradient composite material according to claim 1, characterized in that: The content of pure copper powder in the second gradient composite material is 3wt%, the content of pure copper powder in the third gradient composite material is 5wt%, and the content of pure copper powder in the fourth gradient composite material is 8wt%.
3. The laser additive manufacturing method of the 316L+xCu functionally gradient composite material according to claim 1, characterized in that: The step S1 specifically includes: Step S11, drying the atomized 316L powder and the pure copper powder; Step S12: mechanically mixing the dried atomized 316L powder and the pure copper powder in different proportions in sequence to obtain the first gradient composite material, the second gradient composite material, the third gradient composite material and the fourth gradient composite material.
4. The laser additive manufacturing method of the 316L+xCu functionally gradient composite material according to claim 1, characterized in that: The step S2 specifically includes: The surface of the 316L stainless steel substrate was polished using silicon carbide sandpaper.
5. The laser additive manufacturing method of the 316L+xCu functionally gradient composite material according to claim 1, characterized in that: The laser additive manufacturing equipment comprises a fiber laser, a powder feeder and a protective gas tank. The wavelength of the fiber laser is 1064 nm, and the protective gas tank stores an inert gas.
6. The laser additive manufacturing method of the 316L+xCu functionally gradient composite material according to claim 5, characterized in that: The step S3 specifically includes: Step S31, according to the preset process parameters, under the inert gas output by the protective gas tank, using the fiber laser to scan, melt and deposit the first gradient composite material output by the powder feeder on the 316L stainless steel substrate to obtain a first gradient layer; Step S32, according to the preset process parameters, under the inert gas output by the protective gas tank, using the fiber laser to scan, melt and deposit the second gradient composite material output by the powder feeder on the first gradient layer to obtain a second gradient layer; Step S33, according to the preset process parameters, under the inert gas output by the protective gas tank, using the fiber laser to scan, melt and deposit the third gradient composite material output by the powder feeder on the second gradient layer to obtain a third gradient layer; Step S34, according to the preset process parameters, under the inert gas output by the protective gas tank, use the fiber laser to scan, melt and deposit the fourth gradient composite material output by the powder feeder on the third gradient layer to obtain a fourth gradient layer.
7. The laser additive manufacturing method of the 316L+xCu functionally gradient composite material according to claim 6, characterized in that: The height of the first gradient layer, the height of the second gradient layer, the height of the third gradient layer and the height of the fourth gradient layer are 2.5 mm respectively.
8. The laser additive manufacturing method of the 316L+xCu functionally gradient composite material according to claim 5, characterized in that: The preset process parameters in step S3 are as follows: the laser power of the fiber laser is 500 W, the laser scanning speed is 600 mm / min, the laser scanning spacing is 0.8 mm, the powder feeding rate of the powder feeder is 14.12 g / min, and the gas delivery volume of the protective gas tank is 15 L / min.
9. The laser additive manufacturing method of the 316L+xCu functionally gradient composite material according to claim 1, characterized in that: After step S3, the following steps are also included: Step S4, analyzing and measuring the 316L+xCu functional gradient composite material.
10. The laser additive manufacturing method of the 316L+xCu functionally gradient composite material according to claim 9, characterized in that: The step S4 specifically includes: Step S41, performing electric spark wire cutting on the 316L+xCu functional gradient composite material to obtain two test samples, and grinding and polishing the two test samples; Step S42, observing the microstructure of one of the two test samples using a scanning electron microscope; Step S43, using an electrochemical three-electrode measurement system to perform a potentiodynamic polarization curve test and an AC impedance spectrum measurement on the other of the two test samples and the comparison sample, wherein the comparison sample is a 316L material obtained by scanning melting deposition of aerosolized 316L powder according to the preset process parameters.
Citation Information
Cited By
Method for compounding heterogeneous metal materials
CN122125221A
